The Mien people's ethnobotanical survey of medicinal plant use in Thailand and Vietnam - PRATEEP PANYADEE; WITTAYA PONGAMORNKUL; TRAN VAN ON; NGHIEM DUC TRONG; PHAM THI LINH GIANG; LE THIEN KIM; ANGKHANA INTA; PANEE SIRISA-ARD; SUNEE CHANSAKAOW (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Panyadee P, Pongamornkul W, Van On T, Trong ND, Giang PTL, Kim LT, Inta A, Sirisa-Ard P, Chansakaow S. 2024. The Mien people's ethnobotanical survey of medicinal plant use in Thailand and Vietnam. Biodiversitas 25: 79-96. This study investigates the ethnomedicinal practices of the Mien people in Thailand and Vietnam, focusing on the diversity of medicinal plant usage and its implications for healthcare and traditional knowledge conservation. Through semi-structured interviews with key informants during transect walks in local forests and home gardens, data on 199 medicinal plant species were gathered, including vernacular names, plant parts used, preparation, and usage methods. Analysis revealed a significant use of these species, with 41 utilized for various health purposes in both countries, treating ailments related to reproductive systems (45 species), body strengthening (29 species), and the digestive system (21 species). In ethnobotanical practices, there were distinct preferences for plant parts. In Thailand, stems (29%), leaves (26%), whole plants (18%), and roots (14%) were predominantly used, while in Vietnam, leaves (29%), stems (24%), whole plants (19%), and roots (11%) were more common. A Spearman's rank correlation showed a strong positive correlation (0.77, p <0.001) between these preferences in both countries. The study documented 81 ailments across 23 health categories. Thailand reported 45 ailments in 20 categories, and Vietnam 67 in 19 categories. Reproductive health, musculoskeletal health, and body wellness strengthening were pivotal, with strong correlations in healthcare practices between the countries (correlation 0.75, p <0.001). Reproductive Health mainly involved postpartum treatment, Musculoskeletal Health focused on pain relief and rheumatism treatments, and Body Wellness Strengthening used plants as tonics and for relaxation. This research underscores the importance of preserving traditional knowledge and the potential of traditional medicine in rural healthcare. It also highlights the scope and focus of the Mien communities' healthcare practices, providing valuable insights for future research and drug development.